The use of veno‐venous extracorporeal membrane oxygenation for massive hemoptysis following a traumatic lung injury: a case report. Issue 1 (15th March 2020) - Sugiyama, Takuya; Ishida, Tokiya; Yokoyama, Hideyuki; Kumada, Yoshibumi; Shinohara, Kazuaki
Abstract : Background: Published reports regarding the use of veno‐venous extracorporeal membrane oxygenation (V‐V ECMO) for massive hemoptysis following a thoracic injury are still scarce. Case Presentation: A 34‐year‐old man developed massive hemoptysis from the right lung after a 2 m fall and being compressed with an iron pipe weighing 500 kg. He was immediately intubated using a double‐lumen tube, and one‐lung ventilation was started. Endotracheal hemorrhage was controlled by sealing the right lumen. V‐V ECMO was initiated to endure the lethal hypoxemia while waiting for the right lung to heal. He came off of V‐V ECMO after 17 days and was discharged on foot on day 46. Conclusion: The strategy of using V‐V ECMO in combination with one‐lung ventilation is useful and should be strongly considered to save lethal massive hemoptysis cases following traumatic lung injury. Abstract : A 34‐year‐old man developed massive hemoptysis after a traumatic lung injury. We report a case of successful application of veno‐venous extracorporeal membrane oxygenation in combination with one‐lung ventilation to save lethal massive hemoptysis in trauma.